Burden and trends of drug use disorders in young adults: global insights from GBD 2021 - Su, Xin; Fan, Teng; Quan, Qi; Kan, Jun; Liu, Zeyu; Zhang, Bei; Huang, Yuanyuan (Frontiers in Psychiatry, 2025)
BackgroundDrug use disorders (DUDs) is a serious global health crisis, particularly affecting adolescents and young people. The increasing prevalence of DUDs has led to the development of chronic diseases, including cancer, although it has significant impacts on health and life, it is often overlooked in research.MethodThis study utilized GBD 2021 data to assess the burden of four drug use disorders in the young adult population. The data, covering 1991 to 2021, included metrics such as age-sex-year incidence, prevalence, deaths, and disability-adjusted life years (DALYs). Age-standardized rates were used for comparing burden across years and regions, and joinpoint analysis evaluated trends. The Bayesian Age-Period-Cohort model was employed to project future burden. The study also examined the relationship between DUDs burden and socio-economic conditions using the Social Development Index (SDI) and stratified data by WHO regions. Additionally, population attributable fractions were calculated within the GBD comparative risk assessment framework.ResultsCannabis use disorder (CUDs) emerged as the most prevalent, the ASPR was 617.22/100,000 in 2021. The highest age-standardized mortality rates (ASMR) and age-standardized DALYs rates (ASDR) was observed in OUDs, at (1.46 [1.37-1.55]) and (236.61[185.21-292.47]), respectively. The region of the Americas accounted for the largest proportion of this burden. Opioid use disorders (OUDs) exhibited a notable rising trend, with the age-standardized prevalence rate (ASPR) of 359.62/100,000 in 2021, with a concentration primarily in the European region and the region of the Americas. Male had a higher burden of DUDs than female in the young adults. The burden of DUDs was mainly concentrated under the age of 25, especially CUDs and OUDs. The ASMR and ASDR of DUDs also showed significant growth trends in high SDI areas. Drug use’s contribution to cancer risk, particularly liver cancer due to hepatitis C virus (HCV), had been progressively increasing.ConclusionsThe burden of OUDs and CUDs, continued to escalate annually, especially among young adult males who face heightened risks. Notably, drug use is increasingly contributing to liver cancer mortality and DALYs, emphasizing the urgency of interventions. This study provides evidence for evaluating the burden transfer between different demographic data.